Rajiv Gandhi's assassination : the mystery unfolds - Dalal, Ramesh (New Delhi : UBSPD, 2001)
Sequence of political events that allegedly led to the assassination of Rajiv Gandhi, b. 1944, former prime minister of India.
Includes index.
Annexures in English, Hindi, and Panjabi.
Keywords: Prime ministers -- Assassination -- India; India -- Politics and government -- 1977-